How Restorative are You? Introducing the Restorative Index - Olson, Jeremy (Victims & offenders, 2022)
Restorative justice (RJ) currently has no method of quantitatively determining if a program is restorative and assessing how restorative it may be. Due to confusion in RJ definitions and increased attention and funding in RJ, this gap has left RJ open to co-option by punitive systems. Co-option would leave many interpersonal harms unrestored. The present paper reduces that co-option threat by introducing the Restorative Index (RI). We review the philosophy, definitions, and elements of RJ. We then translate those definitions and elements directly into the RI. We demonstrate ratings on the RI using an existing program. Use of the RI will improve program development, implementation, outcome assessments, and funding decisions.